Bodily cleanliness in modern nursing - Boge, Jeanne (Nursing philosophy, 2013)
Why are bodily washing practices the way they are in nursing? Michel Foucault argues that modern democratic societies discipline human bodies in accordance with political interests. In the extension of that argumentation we will show that bodily cleanliness in modern nursing may have been used as a disciplining tool. The first part of our discussion takes as its point of departure the second half of the 19th/the beginning of the 20th centuries, the period in which modern nursing emerged. At that time scientific theories on hygiene seem to have legitimized the political effort to produce a clean, pleasant-smelling, decent, obedient, and productive population. Doctors, nurses and teachers played important roles in the implementation of hygienic bodily washing practices. The second part of the discussion focuses on the post-War period. At that time humanistic needs theories seem to have legitimized political argumentation for independent patients who washed themselves if possible. Those who could not manage on their own, should, as far as possible, be washed by cheaper staff, so that nurses could concentrate on medical treatment. Finally we argue that present day bodily washing practices in nursing are in accordance with the norms of appearance and smell that arose in the second half of the 19th and the first part of the 20th centuries. We further argue that staff with little or no education perform much of the bodily nursing work. Self-care seems to be of interest only when it reduces public expenses.